AN ANALYSIS OF THE FULFILMENT OF CHILDREN'S RIGHTS IN SCHOOL DROPOUT CASES IN THE TIN MINING AREA OF SOUTH BANGKA - Saptahadi, Yundra; Yandi, Yandi (LPPM STIH Putri Maharaja, 2025)
This research examines the fulfilment of children's educational rights guaranteed in the Indonesian constitution in the case of school dropouts at SMK Negeri 1 Tukak Sadai, South Bangka Regency, which is influenced by tin mining activities. Using a socio-legal approach, this research examines the gap between constitutional guarantees and the social realities faced by children in tin-mining areas. This study uses in-depth interviews, field observations, and an analysis of relevant legal documents. The findings indicate that the combination of economic, social, and cultural factors, along with tin mining activities, plays a significant role in the high dropout rate at SMK Negeri 1 Tukak Sada. The implementation of educational rights guarantees in the constitution has not been optimal due to weak cross-sectoral coordination, lack of specific policies for mining areas, and inadequate supervision. This research recommends strengthening policies to protect children's educational rights in mining areas through an integrative approach involving the government, mining companies, schools, and the community to achieve the fulfilment of constitutionally guaranteed educational rights.